Tetrathiomolybdate Treatment Leads to the Suppression of Inflammatory Responses through the TRAF6/NFκB Pathway in LPS-Stimulated BV-2 Microglia - Wang, Zhuo; Zhang, Ya-Hong; Guo, Chuang; Gao, Hui-Ling; Zhong, Man-Li; Huang, Ting-Ting; Liu, Na-Na; Guo, Rui-Fang; Lan, Tian; Zhang, Wei; Wang, Zhan-You; Zhao, Pu (Frontiers in Aging Neuroscience, 2018)
Although the positive relationship between copper and Alzheimer's disease (AD) was reported by a lot of epidemiological data, the mechanism is not completely known. Copper is a redox metal and serves as mediators of inflammation. Because the homeostasis of copper is altered in Aβ precursor protein (APP) and presenilin 1 (PS1) transgenic (Tg) mice, the using of copper chelators is a potential therapeutic strategy of AD. Here we reported a copper chelator, tetrathiomolybdate (TM), is a potential therapeutic drug of AD. We investigated whether TM treatment led to the decrease of pro-inflammatory cytokines in vivo and in vitro, and found that TM treatment reduced the expression of iNOS and TNF-α in APP/PS1 Tg mice through up-regulating superoxide dismutase 1 (SOD1) activity. In vitro, as the activation of microglia secrete a variety of proinflammatory, so we utilized LPS-stimulated BV-2 cells as a inflammatory model cells to detect the anti-inflammation effect of TM and the in vitro data indicated that TM-pretreatment suppressed the ubiquitination of TRAF6 and the activation of NFκB without affecting the expression of TLR4 and Myd88. By detecting the activity of SOD1 and the production of reactive oxygen species (ROS), we found that the anti-inflammation effects of TM can be attributed to its ability to reduce the amount of intracellular bioavailable copper, and the production of ROS which is an activator of the TRAF6 auto-ubiquitination. Hence, our results revealed that TM-treatment can reduce the production of inflammatory cytokines by the suppression of ROS/TRAF6/AKT/NFκB signaling pathway.